PENURUNAN NILAI RUPIAH DAN IMPLIKASINYA TERHADAP KETAHANAN FINANSIAL : PERAN LABA SEBAGAI VARIABEL INTERVENING - Dwi Tri Nilasari; Aulia Sindy Perwirasari (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2025)
This study aims to examine whether the decline in the value of the rupiah currency has an impact on financial resilience with the profit variable as an indirect linking variable (financial resilience) in the midst of an unstable global economic situation and the effect of interest rate cuts by the United States. So that this research is focused on supporting economic life, especially MSMEs in the community. The research method used in this research is quantitative research. The data collection process in this study was carried out by filling out a questionnaire by MSMEs. Respondents in this study were 37 MSMEs located in the Cempaka market, Kumai District, West Kotawaringin Regency. Hypothesis testing was carried out with SMART PLS 3.0. The results of the study show that the decline in the value of the rupiah directly affects financial resilience as well as the profit variable as a link. However, indirect testing shows that profit does not have a significant effect on the value of the rupiah and financial resilience. So that profit cannot be the role of mediator between the two variables.